Wireless Biomedical Sensor Network Reference Design Based on the Intel® Edison Platform - Lin, Tianyu (Kansas State University, 2017)
A reference design for a wearable, wireless biomedical sensor set has been a long-term need for researchers at Kansas State University, driven by the idea that a basic set of sensor components could address the demands of multiple types of human and animal health monitoring scenarios if these components offered even basic reconfigurability. Such a reference design would also be a starting point to assess sensor performance and signal quality in the context of various biomedical research applications. This thesis describes the development of a set of wireless health monitoring sensors that can be used collectively as a data acquisition platform to provide biomedical research data and to serve as a baseline reference design for new sensor and system development. The host computer, an Intel Edison unit, offers plug-and-play usability and supports both Wi-Fi and Bluetooth wireless connectivity. The reference sensor set that accompanies the Intel Edison single-board computer includes an electrocardiograph, a pulse oximeter, and an accelerometer/gyrometer. All sensors are based on the same physical footprint and connector placement so that the sensors can be stacked to create a collection with a minimal volume and footprint. The latest hardware version is 3.1. Version 1.0 supported only a pulse oximeter, whereas version 2.0 included an electrocardiograph, pulse oximeter, and respiration belt. In version 3.0, the respiration belt was removed, and accelerometers and gyroscopes were added to the sensor set. Version 3.1 is a refined version of the latter design, where known hardware bugs were remedied. Future work includes the development of new sensors and casing designs that can hold these sensor stacks.
Keywords: Electrocardiogram (ECG); Wireless Biomedical Sensor; Pulse Oximeter; Accelerometer Gyrometer